The like economy : how businesses are making money with Facebook - Carter, Brian, internet marketing consultant (Que, 2012)
Earn Big Business Profits on Facebook • Practical, specific, proven, and revenue-oriented! • Packed with real-world lessons you can use right now Here's your complete, start-to-finish plan for making money on Facebook! Brian Carter offers step-by-step techniques and practical lessons drawn from his 11 years of experience helping companies double and triple their revenue online. This revenue-focused book is packed with up-to-date ideas and proven solutionswith all the details you need to execute crisply, avoid costly mistakes, and reap big profits. You'll learn how to identify your best Facebook profit opportunities...craft Facebook programs that reflect your unique offerings, brands, and customers...use Facebook to supercharge your existing marketing programs...attract super-affordable targeted clicks and fans with Facebook ads...repel negative "brand-bashers."...increase visibility...deepen your customer interactions...translate "community" into cash! Your customers aren't just "on" Facebook: Nowadays, that's where they're most engaged. That's where you need to reach them. Marketing on Facebook is no longer optional--but the field is cluttered with hype, foolishness, and "fake" solutions that don't deliver results. This book gives you what you really need: a complete, proven, step-by-step plan for maximizing your ROI on Facebook. Building on techniques he's used to help dozens of companies supercharge their online revenues, Brian Carter delivers up-to-the minute, ground-level solutions that work. The devil's in the details, so Carter gives you all the specifics you need to implement these strategies quickly and cost-effectively. Whether you're an entrepreneur, marketer, or social marketing specialist, this book will help you attract more visitors and fans at lower cost...convert more visitors into profitable buyers...repel "brand-bashers" and encourage positive, productive posts...continually measure and optimize your performance...transform your Facebook presence from an experiment into a robust, highly profitable market channel. • Leverage the five most direct routes to Facebook profits Construct your most powerful Facebook marketing mix • Transform FaceLookers into FaceBuyers Master the 13 best Facebook sales and influence techniques • Avoid six missteps that destroy Facebook marketing programs Learn from the pioneers' costly mistakes • Achieve non-revenue goals while you're earning bigger profits Gain branding and positioning benefits at the same time as you'r...